Successful technological integration for competitive advantage in retail settings - Pantano, Eleonora (Advances in E-Business Research (AEBR) Book Series, 2015)
"This book examines the various effects of changing markets and subsequently how these changes cause retailers to meet consumer demand by integrating more sophisticated, advanced innovations in their daily practices"..